Acute hepatitis B in blood donors over a 5‐year period in England and North Wales: who is getting infected?. Issue 6 (26th November 2013) - Rosenberg, Gillian K.; Lattimore, Sam; Brailsford, Susan R.; Hewitt, Patricia E.; Tettmar, Kate I.; Kitchen, Alan D.; Ijaz, Samreen; Tedder, Richard S.
<x xml:space="preserve">Abstract</x> Background Hepatitis B virus (HBV) remains the infection most frequently recognized by donation testing in blood donors. It is usually a persistent infection and mostly reflects the country of origin of the donor or the donor's family. There are, however, a minority of acute infections and this study undertook their phylogenetic analysis to determine the likely source of infection. Study Design and Methods Plasma samples from 11 donors donating between July 2005 and June 2010, whose test results revealed recent infection with hepatitis B, were available for further analysis. Plasma DNA was extracted, amplified, sequenced, and analyzed phylogenetically. Donor and virus characteristics were compared with the overall demography of all hepatitis B–infected donors attending over the same period. Results Three of the 11 individuals were first‐time donors. Nine were male, of whom eight were white British. All had serum markers of very recent infection. Only two indicated known HBV exclusion risk factors at postdonation discussion not declared previously. Genotype A was present in seven, Genotype B in two, and Genotype C in two, contrasting with the pattern in persistently infected persons in the United Kingdom. A single A2 strain was identified in six of the white British male donors, suggesting epidemiologic linkage. Conclusion Phylogenetic analysis of HBV‐infected donors performed in real time can potentially lead to identification of undeclared risk factors that donor health questionnaires may fail to identify.